MEDICAL AND CLIMATIC STUDIES OF LIVING CONDITIONS AND THEIR IMPACT ON HUMAN HEALTH - Illiash, O.E.; Solovieva, N.V.; Soloviev, V.V.; Holik, Yu.S.; Chukhlib, Yu.A. (World of Medicine and Biology, 2020)
In recent years, living conditions of people and potential of their health are increasingly dependent on changes in climatic factors. Therefore, studies in the field of medical and climatic research are becoming more relevant. This paper presents the results of medical and climatic study of living conditions in the territorial boundaries of Poltava for the period of 2006–2019, which were carried out on the basis of bioclimatic characteristics by determining the people's thermal sensitivity degree of the environment. To concretize the obtained results, we carried out a sociological survey of a control group of Poltava residents on the thermal sensitivity of the environment in different seasons of the year. A comparative evaluation of the obtained calculation data with the survey data was performed, which allowed us to carry out a deeper analysis of the causal relationships between the thermal sensitivity of the human body and climatic indices and to draw appropriate conclusions.
Keywords: medical and climatic studies; bioclimatology; human health; thermal comfort